The struggle for national independence in its international setting : its economic and political background and its manifestation in the Fourth Committee of the United Nations General Assembly - Lumsden, Geoffrey S (Rhodes University, Faculty of Commerce, Department of Economics, 2026)
The decade following the close of the Second World War has been dominated throughout by the clash of political power of the United States and the Soviet Union. Their wartime alliance has crumbled. New, antagonistic alliances have come into existence. The so-called 'EastWest' split, polar in its effect, has forced the admission that prospects of stable peace depend on how successfully bridges can be made to span the gulf. This over-riding and pervading reality has blinded us to the importance of another struggle, which is everywhere mounting in force and intensity and which history may well record as a dominant theme of the twentieth century -- the world-wide struggle for independence. In some cases it has produced revolution and violence: full-scale wars have been fought in its cause in Indonesia and Indo-China
Keywords: United Nations. General Assembly; Self-determination, National; Sovereignty; Economics -- Political aspects; Economic policy